Modeling the Effects of Drift Shell Splitting in Two Case Studies of Simultaneous Observations of Substorm‐Driven Pi1B and IPDP‐Type EMIC Waves. Issue 10 (23rd October 2022) - Salzano, Michelle; Lessard, Marc R.; Noh, Sungjun; Kim, Hyomin; Waters, Colin; Engebretson, Mark J.; Horne, Richard; Clilverd, Mark; Kadokura, Akira; Tanaka, Yoshimasa; Kim, Khan‐Hyuk; Matzka, Jürgen; et al.
Abstract: Intervals of pulsations of diminishing periods (IPDPs) are a subtype of electromagnetic ion cyclotron (EMIC) waves that can be triggered by substorm onset. Pi1B waves are ultralow frequency (ULF) broadband bursts that are well correlated with substorm onset. IPDPs are associated with increased fluxes of 40–60 keV substorm‐injected protons which undergo gradient‐curvature drifting and interact with the cold plasmasphere population. While particle trajectories and the generation of IPDPs have been modeled in the past, those models neglect the role that drift shell splitting plays in the process. This research investigates the different pathways that Pi1B and IPDPs take from their shared origin in substorm onset to their distinct observations on the ground, including the effects of drift shell splitting en route. This paper presents two case studies using data from an array of four ground‐based Antarctic magnetometers that cover the evening sector, as well as in situ magnetometer data, proton fluxes, and proton pitch angles from the Van Allen Probes spacecraft. These observations identify a separation in geomagnetic latitude between Pi1Bs and IPDPs, and pinpoint a separation in magnetic local time (MLT). From these observations we model the drift shell splitting which injected particles undergo post‐onset. This study shows that simulations that incorporate drift shell splitting across a full injection front are dominated by injection boundary effects, and that the inclusion of drift shell splitting introduces a slight horizontal component to the time axis of the time–frequency dependence of the IPDPs. Key Points: Pi1Bs and IPDPs observed from Antarctic ground stations occur simultaneously with particle injections from substorm onset We simulate the trajectories of particle injections from substorm onset as subject to drift shell splitting across a full injection front Particle trajectories are dominated by injection boundary effects, but drift shell splitting affects the time‐frequency features of IPDPs